The Alliance–Outcome Association in Couple Therapy: A Common Fate Model. Issue 3 (26th May 2021) - Quirk, Kelley; Drinane, Joanna M.; Edelman, Anna; Chow, Daryl; Lim, Joline; Chandra, Diana; Miller, Scott; Owen, Jesse
Abstract: The working alliance has been shown to be a robust predictor of couple therapy outcomes. However, there are still questions regarding the best way to conceptualize and analyze the association between the alliance and outcomes in the couple therapy context. This study presents results from a relatively novel analytic approach for evaluating the alliance and therapy outcomes via the shared influence model (i.e., common fate statistical methodology) with 93 couples who had at least three sessions. Examining the alliance in couple therapy this way allows for nuance in conceptualizing the process of the alliance among partners and the therapist in couple therapy. Empirically, the question that remains is whether the shared experience of the alliance between partners is a stronger predictor of therapy outcome as compared to the unique individual experiences of the alliance. This approach has not yet been utilized to model the couple alliance–outcome association. Results revealed that the shared influence model demonstrated a significant association between the alliance and therapy outcome. Specifically, the couple‐level alliance construct was adequately represented from the partners' alliance ratings with the therapist, and couples that report higher shared alliance experiences were also likely to have better therapy outcomes. These findings suggest that conceptualizing and analyzing the alliance at the couple level may be strongly advantageous. Implications for research and practice are provided. Resumen: Se ha demostrado que la alianza terapéutica es un predictor fiable de los resultados de la terapia de pareja. Sin embargo, aún quedan preguntas con respecto a la mejor manera de conceptualizar y analizar la asociación entre la alianza y los resultados en el contexto de la terapia de pareja. Este estudio presenta resultados de un enfoque analítico relativamente innovador para evaluar la alianza y los resultados de la terapia mediante el modelo de influencia compartida (p. ej.: metodología estadística del destino común) con 93 parejas que tuvieron al menos tres sesiones. Analizar la alianza en la terapia de pareja de esta manera permite matices a la hora de conceptualizar el proceso de la alianza entre los integrantes de la pareja y el terapeuta en la terapia de pareja. Empíricamente, la pregunta que queda pendiente es si la experiencia compartida de la alianza entre los integrantes de la pareja es un predictor más fiable de los resultados de la terapia en comparación con las experiencias individuales únicas de la alianza. Este enfoque aún no se ha utilizado para interpretar la asociación entre la alianza de la pareja y los resultados. Los resultados revelaron que el modelo de influencia compartida demostró una asociación significativa entre la alianza y los resultados de la terapia. Específicamente, el constructo de la alianza a nivel de la pareja se representó adecuadamente a partir de las valoraciones de la alianza de los integrantes de la pareja con el terapeuta, y las parejas que informan más experiencias de alianza compartida también fueron propensas a tener mejores resultados en la terapia. Estos datos sugieren que puede ser enormemente ventajoso conceptualizar y analizar la alianza a nivel de la pareja. Se explican las consecuencias para la investigación y la práctica. 摘要: 关系联盟可以比较准确地预测伴侣治疗的结果，这都是已经被证实过了的。然而，在伴侣治疗的背景下，如何理解和分析这种联盟与治疗结果之间的关系，依然还存在问题。本研究采用了一种相对新颖的分析方法，通过共享影响模型 (即共同命运统计方法)来评估联盟和治疗结果。研究对象为93对至少参加过三次治疗会谈的伴侣。通过这种方式来考察伴侣治疗中的联盟，可以认识更多伴侣和伴侣治疗师之间的联盟过程中出现的细微差别。在实证经验上，仍然存在的问题是伴侣共同经历的联盟关系是否会比独特的个人单方面体验的联盟关系更能预测治疗结果。这种方法还没有被使用在建立伴侣联盟‐结果的关系模型中去。研究结果显示，共同影响模型能展现联盟与治疗结果之间的显著关联。具体而言，从伴侣与治疗师的联盟评级中，可以充分地反映出伴侣层面的联盟关系构建。如果报告的共同经历的联盟体验越高，伴侣治疗的结果也可能更好。这些发现表明，对伴侣层面的联盟进行概念化的理解和分析可能非常有利。本论文对研究和实践提都供了启示。